The features of vegetative regulation of heart in athletes and team sports athletes - Шевчук, Т. Я.; Романюк, А. П. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The article describes the features of the vegetative regulation of the heart rate in athletes. There have been examined athletes and team sports athletes, using heart rate variability (HRV) techniques. Main temporary, spectral and HRV (by R.M.Baevsky) indices were studied as well as predominant type of cardiac activity regulation. Team sports athletes were characterized by a decrease in temporary indices, except for the heart rate. Analysis of spectral indexes showed an increase of the indices in athletes. Sympathetic type of vegetative regulation was dominant in team sports athletes, and parasympathetic type was revealed in athletes. The results show a decrease in the mechanisms of self-regulation and activation of energy-metabolic exchange centers in team sports athletes. Athletes demonstrated a high level of physical fitness and a marked decrease in the activity of the central regulation contour.